Clinical Significance of MPO-ANCA in Eosinophilic Granulomatosis With Polyangiitis: Experience From a Longitudinal Chinese Cohort - Liu, Suying; Han, Linna; Liu, Yanhui; Yang, Jun; Zhang, Yu; Li, Mengtao; Tian, Xinping; Zeng, Xiaofeng; Wang, Li; Zhang, Fengchun (Frontiers in Immunology, 2022)
Objectives The aim of this study is to investigate the clinical significance of myeloperoxidase (MPO)–antineutrophil cytoplasmic antibody (ANCA) on eosinophilic granulomatosis with polyangiitis (EGPA) from a longitudinal Chinese cohort. Methods A total of 120 patients with EGPA were consecutively enrolled and followed up. Two patients with PR3 ANCA was excluded and our analysis focused on the 118 patients with EGPA. On the basis of MPO-ANCA status, baseline clinical manifestations, treatment, and outcomes were analyzed. Logistic regression analysis was performed to analyze the independently associated factors for renal involvement. Results ANCA positivity was observed in 24.2% of patients with EGPA. Patients with MPO-ANCA accounted for 20.8%. Patients with positive MPO-ANCA had higher levels of erythrocyte sedimentation rate (ESR), C-reactive protein, Birmingham Vasculitis Activity Score (BVAS), higher ratios of fever, myalgia, renal involvement, and biopsy-proven vasculitis. Heart manifestations and asthma were more common in patients with negative ANCA. Baseline MPO-ANCA titers positively correlated with ESR, eosinophil count, and BVAS and were higher in patients with methylprednisolone pulse. Among patients with renal involvement, patients with positive MPO-ANCA had higher proportions of female, fever, biopsy-proven vasculitis, and faster ESR; patients with negative ANCA developed more skin and cardiac involvement. MPO-ANCA positivity, male, and ear involvement were the independent factors associated with renal involvement. Intravenous cyclophosphamide and immunoglobulins were prescribed more frequently in patients with positive MPO-ANCA. Conclusion In this cohort, patients with positive MPO-ANCA and negative ANCA displayed distinct clinical features, suggesting that MPO-ANCA might be a valuable biomarker for EGPA stratification. Baseline MPO-ANCA level correlated positively with disease activity of EGPA. MPO-ANCA was a significant independent factor associated with renal involvement.